2005
DOI: 10.1021/la047629q
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Switch of Permeability for Polyelectrolyte Microcapsules Embedded with Co@Au Nanoparticles

Abstract: We explored using a magnetic field to modulate the permeability of polyelectrolyte microcapsules prepared by layer-by-layer self-assembly. Ferromagnetic gold-coated cobalt (Co@Au) nanoparticles (3 nm diameter) were embedded inside the capsule walls. The final 5 mum diameter microcapsules had wall structures consisting of 4 bilayers of poly(sodium styrene sulfonate)/poly(allylamine hydrochloride) (PSS/PAH), 1 layer of Co@Au, and 5 bilayers of PSS/PAH. External alternating magnetic fields of 100-300 Hz and 1200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
253
2
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(268 citation statements)
references
References 44 publications
4
253
2
9
Order By: Relevance
“…As a result, the macroporous ferrogels demonstrate very large deformation, volumetric change, and water convection under applied magnetic fields, in contrast to the minimal values of conventional nanoporous ferrogels. Furthermore, it is generally difficult for nanoporous ferrogels to release drugs with high molecular weight, such as proteins and plasmid DNA, due to the limited mobility of these drugs in the nanopores (32)(33)(34)(35)(36)(37). The connected macropores in the new ferrogel enable the rapid transport of various drugs ranging from small molecules such as mitoxantrone to very large molecules such as the protein SDF-1α and plasmid DNA out of the gel, upon magnetic stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the macroporous ferrogels demonstrate very large deformation, volumetric change, and water convection under applied magnetic fields, in contrast to the minimal values of conventional nanoporous ferrogels. Furthermore, it is generally difficult for nanoporous ferrogels to release drugs with high molecular weight, such as proteins and plasmid DNA, due to the limited mobility of these drugs in the nanopores (32)(33)(34)(35)(36)(37). The connected macropores in the new ferrogel enable the rapid transport of various drugs ranging from small molecules such as mitoxantrone to very large molecules such as the protein SDF-1α and plasmid DNA out of the gel, upon magnetic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrogels consisting of magnetic particles embedded in polymer gels have been intensively investigated, due to the broad application and clinical acceptance of magnetic particles and magnetic fields (26)(27)(28)(29)(30)(31). Recent studies have shown controlled release of a number of drugs from ferrogels subject to magnetic fields (32)(33)(34)(35)(36)(37). Ferrogels have also been made biodegradable (38) and injectable (39).…”
mentioning
confidence: 99%
“…The plausible reason was due not only to the volume shrinkage at higher temperature but also to the change in the pore structure of the nanospheres under HFMF. Lu et al 4 reported on ferromagnetic cobalt nanoparticles coated with gold shells (Co@Au nanopaticles) embedded into polyelectrolyte capsules. They demonstrated that such magnetic capsules resulted in an increase of wall permeability due to magnetostatic interaction between nanoparticles under oscillating magnetic field.…”
Section: Drug Delivery Test By Hfmfmentioning
confidence: 99%
“…For instance, Cong et al (2010) have prepared magnetic-functionalized rGO sheets through high-temperature decomposition of Fe(acac) 3 precursor in polyol, (3) precise controlling the loading amount of Fe 3 O 4 , and then, tailoring the properties of resultant hybrids for desired application is a main challenge as well (Yang et al 2009) and (4) another major challenge is because of easy oxidation/dissolution of the pure Fe 3 O 4 NPs when using these nanomaterials, specially in acidic solutions. To overcome these problems and specifically to protect the magnetic NPs against oxidation, a shell structure is often introduced, including silica (Zhu et al 2011a, b) polymer (Shin and Jang 2007) and noble metals (Cho et al 2005;Lu et al 2005). And recently, covalent attachment of Fe 3 O 4 NPs onto GO has been developed which provides better stability, accessibility, selectivity and less leaching.…”
Section: Introductionmentioning
confidence: 99%